Analisis Determinan Kejadian Laserasi Jalan Lahir Pada Ibu Bersalin di RS Islam Banjarmasin - Mirawati; Rr. Sri Nuriaty Masdiputri; Mahfuzhah Deswita Puteri (Sistem Informasi, 2022)
Complicated deliveries are prone to result in maternal and fetal death. Postpartum hemorrhage is the main cause of maternal death, one of which is caused by lacerations in the birth canal. There are several things that can cause this. This study aims to analyze the determinants of the incidence of birth canal lacerations in women giving birth. The research method used a case control method, namely comparing perineal lacerations with episiotomy as cases with spontaneous perineal lacerations as controls. The research was conducted at the Islamic Hospital of Banjarmasin. The sampling technique used simple random sampling with a ratio of 1:2, namely 58 people in the case group and 29 people in the control group so that the total sample was 87 people. The analysis was carried out with chi square. The results showed that there was an effect of parity on birth canal lacerations with p value: 0.003 < (0.05), while age and birth weight had no effect on birth canal lacerations. Parity multigravida are 4.8 times more prone to laceration of the birth canal than primigravida.